Diagnostic Accuracy Of Placental Thickness Measured By Ultrasonography In The Detection Of Intrauterine Growth Restricted (IUGR) Babies Keeping Actual Birth Weight As Gold Standard - Farkhanda Jabeen; Madiha Farhan; Maryam Amjad; Aeisha Begum; Nadia Gul; Salma Umbreen (Journal of Rawalpindi Medical College)
Objective: To determine the diagnostic accuracy of the placental thickness measured by ultrasound in detecting IUGR babies keeping actual birth weight as the gold standard.